Critical roles of NLRP3 inflammasome in IL-1β secretion induced by Corynebacterium pseudotuberculosis in vitro. (December 2019) - Zhou, Zuoyong; Li, Hexian; Tian, Shangquan; Yi, Wenyi; Zhou, Yang; Yang, Haoyue; Li, Xiao; Wu, Bi; Li, Xiaoxia; Wu, Junjun; Wang, Zhiying; Hu, Shijun; et al.
Highlights: C. pseudotuberculosis induces IL-1β secretion in macrophages independent of AIM2. C. pseudotuberculosis induces IL-1β secretion dependent on NLRP3 inflammasome. NF-κB and p38MAPK are involved in C. pseudotuberculosis induces IL-1β secretion. C. pseudotuberculosis induces IL-1β secretion is partially dependent on TLR4. NLRP3 inflammasome restrict C. pseudotuberculosis replication in macrophages. Abstract: Corynebacterium pseudotuberculosis is a prominent human and animal pathogen causing chronic inflammatory diseases. Interleukin-1β (IL-1β) is involved in the response to such pathogenic infections. However, the mechanism by which IL-1β is secreted during C. pseudotuberculosis infection remains unclear. This study aimed to investigate the mechanism underlying IL-1β secretion by macrophages infected with C. pseudotuberculosis . Herein, we firstly revealed that nucleotide-binding oligomerization domain-like receptor family, pyrin domain containing 3 (NLRP3), apoptosis-associated speck-like protein containing a CARD (ASC) and caspase-1 (Casp1) play critical roles in IL-1β secretion rather than IL-1β precursor (pro-IL-1β) expression in C. pseudotuberculosis -infected macrophages. Toll like receptor 4 (TLR4) is partially involved in IL-1β secretion, while absent in melanoma 2 (AIM2) is not involved in IL-1β secretion by C. pseudotuberculosis -infected macrophages. In addition, nuclear factor kappa B (NF-κB) and p38 mitogen-activated protein kinases (p38 MAPK) inhibitors almost attenuated IL-1β secretion, implying that NF-κB and p38MAPK pathway are involved in IL-1β secretion in C. pseudotuberculosis- infected macrophages. Furthermore, C. pseudotuberculosis were significantly more numerous in Nlrp3 −/−, Asc −/−, and Casp- 1 −/− macrophages than in WT macrophages at 24 h after infection ( P < 0.05), indicating that NLRP3 inflammasome components limit C. pseudotuberculosis replication in macrophages. Together, these data provide novel insights into the mechanisms underlying IL-1β secretion in C. pseudotuberculosis -infected macrophages and further the current understanding of the host pro-inflammatory immune response against this pathogen.